A exposição como experiência pedagógica de sentidos - Giovanna Antônia Vichiato Lima (2016)
This research addresses some educational practices of museums and proposes the use of some of their techniques for the preparation of exhibitions at school. In the theoretical part we seek dialogue with authors who deal with sensibility development and appreciation of the use of experience in the teaching-learning and encouraging the rescue of material objects representatives of culture, memory and identifify for the pedagogical work. The resulting product of our research is a guide to help k-12 teachers to develop exhibitions at school, providing aestheticexperiences with varied thematic suggestions. This guide, which is contextualized in the 2nd and presented in the 3rd chapter, will be made available on a website. Its potential use and limitations are discussedin the final chapter of this dissertation.